Optimization of Information and Communication Technology: Digital Innovation for Sustainable Agriculture - Nurhidayat, Diat; Sukmawati, Dalia (Biospecies, 2024)
The development of the times in the generation Z era, uses information technology so much that it cannot be separated from today’s daily life. This requires us to increasingly utilize this technology to provide positive impacts rather than negative effects. One use that can be used in the field of biology is to provide digital innovation to help people understand how to learn about oyster mushroom cultivation by the community. Fungi are a group of multicellular eukaryotic fungi with body parts consisting of a base. The group of fungi that have a basidium or are known as fruiting bodies are a group of macroscopic fungi. This group of macroscopic fungi has very high nutritional value. High protein and cellulase are one of the nutritional values contained in these fungi. Macroscopic fungi are often found in forest areas or plantations in rural areas. Edible mushrooms are a food ingredient that contains complete nutrition. Fungi can also be used as a medicinal ingredient. Ling-zhi fungus (Ganoderma sp.) is an ingredient in anticancer drugs, increasing fitness, lowering blood sugar, lowering cholesterol, destroying carcinogens, and antibacterial. Shiitake (Lentinus edodes), maitake (Grifola frondosa) and oyster (Pleurotus sp.) mushrooms have been used as antimicrobial, anti-inflammatory, antioxidant, anti-cholesterol, anti-cancer, antiviral and immunomodulator (Wasser, 2002). The benefits and knowledge regarding the potential of large mushrooms have not been well explored. One of the efforts that will be made in community service in Rajadesa village is to provide knowledge to the surrounding community to utilize the potential of natural resources around the village in order to cultivate large mushrooms, namely Pleurotus sp. The potential for villages with cold temperatures can be used as a place for mushroom cultivation coupled with the optimization of simple information technology to assist in the extension process. The results of the technological innovation used in the service will be carried out for two days with the education stage on how important it is to have the ability to cultivate mushrooms. The next stage is counseling regarding techniques for cultivating large mushrooms by utilizing the natural potential that exists in the countryside. As a result of the service, it is hoped that the community will have knowledge about the health benefits of mushrooms, the types of mushrooms that can be cultivated and education regarding mushroom cultivation techniques.